No Evidence for Improved Associative Memory Performance Following Process-Based Associative Memory Training in Older Adults - Bellander, Martin; Eschen, Anne; Lövdén, Martin; Martin, Mike; Bäckman, Lars; Brehmer, Yvonne (Frontiers in Aging Neuroscience, 2017)
Studies attempting to improve episodic memory performance with strategy instructions and training have had limited success in older adults: Their training gains are limited in comparison to those of younger adults and do not generalize to untrained tasks and contexts. This limited success has been partly attributed to age-related impairments in associative binding of information into coherent episodes. We therefore investigated potential training and transfer effects of process-based associative memory training (i.e., repeated practice). Thirty-nine older adults (Mage = 68.8) underwent six weeks of either adaptive associative memory training or item recognition training. Both groups improved performance in item memory, spatial memory (object-context binding), and reasoning. A disproportionate effect of associative memory training was only observed for item memory, whereas no training-related performance changes were observed for associative memory. Self-reported strategies showed no signs of spontaneous development of memory- enhancing associative memory strategies. Hence, the results do not support the hypothesis that process-based associative memory training leads to higher associative memory performance in older adults.